2007
DOI: 10.1002/jso.20783
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to rehabilitation of the neurosurgical spine cancer patient

Abstract: The treatment of metastatic spine tumors has evolved significantly over the past 20 years due largely to improvements in magnetic resonance imaging; decompressive surgical techniques, spinal instrumentation, and high-dose conformal radiation. These advances have improved our ability to provide meaningful palliation for patients who often have significant medical and cancer-related issues. Despite technical advances that have improved our ability to maintain neurologic function, stabilize the spine, and prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…Special points Barriers to effective rehabilitation include poor neurologic function, comorbid diseases, overall poor prognosis, and inadequate pain control [31]. Patients who receive rehabilitation have increased life satisfaction, reduced depression, and decreases in pain [12•].…”
Section: Physical/speech Therapy and Exercisementioning
confidence: 99%
“…Special points Barriers to effective rehabilitation include poor neurologic function, comorbid diseases, overall poor prognosis, and inadequate pain control [31]. Patients who receive rehabilitation have increased life satisfaction, reduced depression, and decreases in pain [12•].…”
Section: Physical/speech Therapy and Exercisementioning
confidence: 99%
“…It has been reported that the primary barriers to rehabilitation for cancer patient were the neurological status, their oncologic and medical conditions (in particular their prognosis and the medical stability) and pain. 19 Some of these criteria also represented part of the screening parameters of the units. Obviously the neurological status and the presence of pain do not represent a limitation to the admission of NTSCI patients and this is an advantage of referring patients to specialised SCI units.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 These form the acronym NOMPS -Neurological, Oncologic, Medical, Pain and Support status of the patient. The key aspects of the NOMPS criteria are summarized as follows:…”
Section: Setting Of Rehabilitationmentioning
confidence: 99%
“…5,10,[12][13][14][15][16][17] It is acknowledged that the rehabilitation of patients with tumor presents unique challenges, 18 and this applies especially for those with tumor as the cause of SCDys. 10,16,[19][20][21] Despite the high proportion of people with tumor causing SCDys there has been relatively little written about these patients in terms of the ideal setting for their rehabilitation or recommendations for rehabilitation teams caring for them. 10,16,19,20,22 The objectives of this project were: 1) to provide a brief review of the epidemiology, clinical features and outcomes for patients with SCDys due to tumor, 2) to survey participants attending a workshop on the rehabilitation of people with SCDys due to tumor about the admission practices of their SRU regarding these people and the services available for their rehabilitation, and 3) based on evidence from the literature and our expert opinion, propose practical considerations for staff working in SRU when managing people with SCDys due to tumor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation